The problem of mechanization: Craft, machines, and 'centering' in a Japanese Mingei pottery village. (June 2018) - Paredes, Alyssa
This article provides a conceptual basis for 'centering' the relationship between artisanship and mechanization as one would in pottery making. Critical theory dichotomizes handwork from machine-work, emphasizing the division between non-alienated and alienated labor, authenticity and inauthenticity, and experiential resonance and capitalist fetishism. The author demonstrates the theoretical shortcomings and social repercussions of these dualisms through a study of Onta, a Japanese pottery village associated with the mingei folkcraft movement. Tied to ideals of cultural authenticity predicated on the refusal to mechanize, Onta's reputation came into question during the 'Problem of Mechanization' debate, when craftspeople announced a request to introduce modern machinery into their craft making patterns. Reflecting on the ways artisanal and industrial technologies have been imagined, this article poses the question: Do certain mechanical systems exert too much force to enter into centered relationships with humans?